2010
DOI: 10.1021/ef100498u
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Lubricity, Viscosity, and Cold-Flow Properties of Alcohol−Diesel Blends

Abstract: Alcohols have an interesting potential as blending components for diesel fuels because of their capacity to reduce soot formation. Because they have increasing routes for their production from renewable sources, they could contribute toward increasing the renewable fraction of these fuels and, therefore, toward reducing the impact of diesel transportation on the global warming effect. To increase the knowledge about the implications of the use of short- and long-chain alcohols/diesel fuel blends in diesel engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
177
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(187 citation statements)
references
References 30 publications
3
177
0
4
Order By: Relevance
“…Properties of acetone are from Ref. [33,34] c Properties of ethanol and butanol are from Ref. [33,35].…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of acetone are from Ref. [33,34] c Properties of ethanol and butanol are from Ref. [33,35].…”
Section: Experimental Methodologymentioning
confidence: 99%
“…[33,34] c Properties of ethanol and butanol are from Ref. [33,35]. Table 2 Composition and nomenclature of fuel blends Composition of fuel blends (volume basis) Designated nomenclature 10% butanol, 90% Jet A-1 B10 30% butanol, 70% Jet A-1 B30 50% butanol, 50% Jet A-1 B50 30% acetone, 60% butanol, 10% ethanol…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The effect of ethanol addition and temperature on the dynamic viscosity of ethanol-diesel blend fuel was investigated by Chen et al (25) The experimental results for E0, E10, E20 and E30 showed that an increase in ethanol fraction and temperature resulted in the decrease of viscosity of the blends. The kinematic viscosity of the e-diesel blends for 0 to 90% in volume was measured at 40 o C by Lapuerta et al (26) With regard to the diesel quality norm EN 590, blends with more than 22% (v/v) ethanol would not satisfied the requirement of viscosities above 2 cSt. Those results are in accordance with the previous work (24) .…”
Section: E-diesel and E-biodiesel Blendsmentioning
confidence: 99%
“…Additionally, in this range, increasing temperatures led to improved lubricities as a consequence of the ethanol evaporation from the lubricating layer. It was also estimated, that the lubricity of the blends decreases with the alcohol content, but this effect is partially compensated by the alcohol volatility (Lapuerta et al 2010b). Torres-Jimenez et al (2011b) research results presents that the addition of ethanol to diesel fuel slightly improves lubricity, as the wear scar is lower.…”
Section: Introductionmentioning
confidence: 96%